AKUNTANSI DANA PENSIUN PROGRAM MANFAAT PASTI TERHADAP LAPORAN KEUANGAN STUDI PADA DANA PENSIUN BANK INDONESIA (DAPENBI) - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA; Fenny Dwi Lestari (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2016)
This study purposesof knowing about implementation the Accounting standards in retirement fund organization called Dana Pensiun. This study analysed qualitatively by comparing the Accounting implementation in Dana Pensiun Bank Indonesia and the Accounting Standards in Indonesia. Source of data are Financial Report provided by Dana Pensiun Bank Indonesia in year 2012 and 2013, also by interview and observation the calculation of retirement fund. The result show that the implementation of Accounting Dana Pensiun Bank Indonesia is accordance with the generally accepted Accounting Standards in Indonesia.